A Teacher Educator's Action Research: Facilitating Preservice Teachers Becoming Writers and Writing Teachers - Merry Boggs (Networks: An Online Journal for Teacher Research, 2002)
Raising test score requirements will not improve writing skills of college students--it will only serve as a gatekeeper, excluding students who cannot write on demand from becoming teachers. My goal as a teacher educator is to find ways to facilitate preservice teachers becoming writers and teachers of writers---not to exclude them from the program. Dr. Glenn Blalock, a writing professor well versed in process writing, agreed that raising the bar on a writing test would not ensure our students improved writing skills, but asserted that providing meaningful writing activities might. I decided that I could create writers' groups with my preservice teachers and focus on authentic teacher writing assignments. By authentic, I mean writing as a teacher. Process writing comes from the actual process that professional writers do to arrive at a final product. Therefore, preservice teachers can learn about teaching writing through experiencing the same process a writer goes through. My instructional goal entailed creating a preservice teacher authentic writing assignment.